Relapse dynamics during smoking cessation: Recurrent abstinence violation effects and lapse-relapse progression - Kirchner, Thomas R. (2011)
Smoking cessation is a process that unfolds over time and is characterized by intermittent lapses. Behavioral relapse prevention interventions commonly assume that lapse-relapse progression is driven by a set of psychological responses known as the Abstinence Violation Effect (AVE; Marlatt & Gordon, 1985), yet efforts to reduce the AVE have generally failed to affect clinical outcomes. We used parametric recurrent event survival analyses to better understand the dynamic relationship between a set of AVE responses to lapsing and subsequent lapse-relapse progression. Participants were 203 smokers who achieved abstinence and subsequently lapsed on one or more separate occasions. Using electronic diaries for ecological momentary assessment, participants responded to items assessing three core components of the AVE (internal attribution of self-blame for the lapse, abstinence self-efficacy and guilt) following a total of 1,001 smoking episodes in near real time. Contrary to hypothesis, neither self-blame, self-efficacy nor guilt following participants’ first lapse predicted relapse, and all three were overshadowed by responses to recurrent lapses that followed. Controlling for responses to their first lapse, responses to each additional lapse did prospectively predict lapse progression, such that drops in self-efficacy were associated with accelerated progression to a subsequent lapse (HR=1.09, CI=1.02–1.15), while increases in internal attributions of blame actually protected against lapsing (HR=0.98, CI=0.97–0.99). Treatment with nicotine patches slowed recurrent lapse progression (HR=0.58, CI=0.48–0.70), but this effect dissipated over multiple lapses, and was moderated by elevated ratings of post-lapse guilt (HR=1.08, CI=1.01–1.18), which predicted accelerated progression within the active patch group, while protecting against lapse in the placebo group. Results highlight the dynamic nature of lapse responses during smoking cessation, indicating that self-efficacy predicts progression from one lapse to the next, while attributions of self-blame and guilt did not influence progression as predicted by the RPM.